2010
DOI: 10.1152/ajpgi.00156.2010
|View full text |Cite
|
Sign up to set email alerts
|

Vagal nerve stimulation protects against burn-induced intestinal injury through activation of enteric glia cells

Abstract: nerve stimulation protects against burn-induced intestinal injury through activation of enteric glia cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
138
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(153 citation statements)
references
References 25 publications
12
138
1
2
Order By: Relevance
“…T/HS has been shown to alter splenic DC maturation at 2 h following resuscitation, supporting the potential for injury to cause rapid changes in tissue DCs (7). Studies evaluating mobilization of intestinal CD103…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…T/HS has been shown to alter splenic DC maturation at 2 h following resuscitation, supporting the potential for injury to cause rapid changes in tissue DCs (7). Studies evaluating mobilization of intestinal CD103…”
Section: Discussionmentioning
confidence: 94%
“…Vagus nerve stimulation (VNS) modulates the inflammatory set point by altering the gut inflammatory response to acute injury, independent of splenic TNF-␣ production (7,29,47). Our previous studies demonstrated that VNS prevents injuryinduced gut barrier failure and alters the DC profile in the ML after trauma/hemorrhagic shock (T/HS) (36).…”
mentioning
confidence: 99%
“…The Tracey laboratories, for example, established that efferent signaling of the vagus nerve acts exclusively via α7nAChR activation in the spleen to regulate systemic cytokine responses to infection in mice (15)(16)(17)(18)(19)(20). Similarly, Costantini and colleagues demonstrated the existence of a similar α7nAChR-dependent regulation of the local inflammatory response in tissues (21)(22)(23)(24)(25)(26)(27). With α7nAChR activation clearly essential to inflammation, not to mention vagus nerve responsiveness and leukocyte function (28,29), we reasoned that it was therefore critical to understand how a human-specific α7nAChR in human leukocytes might influence human leukocyte function, the regulation of its expression and the biological consequences of its expression.…”
Section: Introductionmentioning
confidence: 99%
“…In the enteric nervous system, increases in the expression of glial fibrillary acidic protein (GFAP) and proliferation of glial cells have also been reported in bowel inflammation such as ulcerative colitis [9][10][11][12]. As to the 'neuroendocrine' islet, it remains unclear whether similar reactive cellular responses occur in islet injuries, such as insulitis, in the progression of type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%